Moderate Knowledge and Attitudes Toward Vitiligo Among University Students in Iraq: Pengetahuan dan Sikap Terhadap Vitiligo di Kalangan Mahasiswa di Irak - Awad, Kadhim Jawad (Academia Open, 2024)
Background: Vitiligo is a depigmenting skin condition characterized by the selective loss of melanocytes, leading to amelanotic, nonscaly, chalky-white macules with distinct borders. Despite its prevalence, public knowledge and attitudes toward vitiligo remain under-researched, particularly in educational settings. Knowledge Gap: There is limited research assessing the understanding and attitudes of university students toward vitiligo, particularly in Middle Eastern regions. Aims: This study aims to evaluate the knowledge and attitudes of students at Basrah University’s Bab Al-Zubair complex regarding vitiligo, using a cross-sectional descriptive design. Methodology: A random sample of 300 male and female students participated, responding to a closed-ended questionnaire created from a review of relevant literature. The survey, administered in Arabic, consisted of three parts: sociodemographic characteristics, 16 questions on knowledge, and 7 questions on attitudes toward vitiligo. A three-point Likert scale was used to evaluate responses. Results: The majority of participants demonstrated moderate knowledge of vitiligo, with similar findings in their attitudes, as assessed using an arithmetic mean. Expert validation of the questionnaire ensured the clarity and relevance of its content. Novelty: This study provides the first comprehensive evaluation of university students’ knowledge and attitudes toward vitiligo in Basrah, filling a significant gap in dermatological health education research in the region. Implications: Raising public awareness about vitiligo is crucial to improving the psychological well-being, social integration, and self-esteem of those affected by the condition. These findings highlight the need for educational interventions that can foster better understanding and reduce stigma surrounding vitiligo, particularly in academic settings. Highlights: Students showed moderate knowledge and attitudes toward vitiligo. Validated questionnaire assessed understanding and perceptions. Awareness crucial for social and psychological support of vitiligo sufferers. Keywords: Vitiligo, Knowledge, Attitudes, University Students, Public Awareness